DEVELOPMENT OF A CAREER COUNSELING MODEL TO ADDRESS THE DILEMMA OF PRESTIGE AND EMPLOYMENT DECISIONS OF BACHELOR'S DEGREE GRADUATES - Hafifah, Nur; Muarif, Ahmad Syamsul (Jurnal At-Taujih, 2025)
The phenomenon of the "prestige trap" has become a crucial issue among Indonesian graduates, where the unemployment rate of college graduates reached 5.18% in 2023. This study aims to develop a career counseling model to address the prestige dilemma faced by graduates in career decision-making. The research method uses a qualitative approach with a Research and Development (R&D) design model of Borg & Gall. Participants consisted of 14 informants who were graduates and 3 professional career counselors. Data were collected through semi-structured interviews, observations, and Focus Group Discussions (FGDs), then analyzed using thematic analysis, discourse analysis, and Interpretative Phenomenological Analysis (IPA). The results identified five main themes: discrepancy between academic identity and job market reality, pressure from family expectations (92.9%), social stigma towards certain jobs, internal conflict between economic needs and self-esteem (100%), and limited career knowledge. Based on these findings, the Integrated Career Counseling Model to Address the Prestige Dilemma (CCMPD) was developed, consisting of seven phases: assessment, cognitive restructuring, narrative reconstruction, family and social integration, practical career exploration, resilience building, and follow-up. The model has been validated by experts with a relevance score of 4.67/5.00 and a comprehensiveness score of 4.83/5.00. This research provides a practical contribution in the form of a culturally responsive counseling framework to help graduates reconstruct the meaning of work and make more adaptive and realistic career decisions.